2014
DOI: 10.3382/ps.2014-03898
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of enzymatic hydrolysis of duck blood corpuscle using commercial proteases

Abstract: With the rapid development in livestock and poultry husbandry and increasing shortage of protein sources, recycling of wastes from agricultural and food processing such as blood corpuscles has been regarded as an important industrial procedure to obtain protein sources. This study aimed to find an appropriate method for recycling the considerable amounts of blood corpuscle so as to improve its nutritional value and organoleptic quality. An effective production process for enzymatic hydrolysis of duck blood cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Nevertheless, both ficin and bromelain caused the obvious downward shifts to increased percentages of the small peptides (<10 kDa), indicating the bioactive properties of mung bean protein hydrolysates. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, both ficin and bromelain caused the obvious downward shifts to increased percentages of the small peptides (<10 kDa), indicating the bioactive properties of mung bean protein hydrolysates. 27 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, both cin and bromelain caused the obvious downward shis to increased percentages of the small peptides (<10 kDa), indicating the bioactive properties of mung bean protein hydrolysates. 27 3.3 Structural characterization of mung bean protein hydrolysates 3.3.1 Ultraviolet-visible spectra analysis. Ultraviolet-visible spectroscopy assay was conducted to investigate the absorption spectra of hydrolysates obtained with cin and bromelain.…”
Section: Molecular Mass Distribution Of Hydrolysatementioning
confidence: 99%
“…The protein content was lower than that (89.7%) of whole duck blood powder ( Sorapukdee and Narunatsopanon, 2017 ). On the other hand, the protein content of DBP was higher than that of duck blood corpuscle powder (38.74%) ( Zheng et al., 2014 ). Thus, DBP with high protein content and low lipid is suitable for preparing bioactive peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Kurt and Kilincceker () and Zheng et al. () indicated that the RSM is an important mathematical and statistical technique for optimising the interactions of factors and factor levels and reduce research and production costs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, knowledge of the total experimental system increases (Myers & T A B L E 9 Estimated parameters of second-order response surface models for glycogen content of liver and breast of chicks at day 2 Montgomery, 2009). Kurt and Kilincceker (2011) and Zheng et al (2014) indicated that the RSM is an important mathematical and statistical technique for optimising the interactions of factors and factor levels and reduce research and production costs.…”
Section: Resultsmentioning
confidence: 99%